PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH, MOTIVASI KERJA, DAN KEDISIPLINAN TERHADAP PENGEMBANGAN KARIER GURU SMK DI KABUPATEN BOYOLALI - Priyono, Priyono; Rahayu, Adi (Pascasarjana IAIN Kudus, 2016)
This research aims to know the influence of principal leadership style towards the career development of the vocational high school (SMK) teachers in Boyolali district in the academic year of 2014/2015, influence of the working motivation towards the career development of the SMK teachers in Boyolali district in the academic year of 2014/2015, the influence of the discipline to the career development of the SMK teachers in Boyolali district in the academic year of 2014/2015, work motivation mediate the influence of discipline towards the career development of SMK teachers in Boyolali district in the academic year of 204/2015 and the discipline mediate the principal leadership style influence towards the career development of SMK teachers in Boyolali district in the academic year of 2014/2015. This research uses a quantitative research design. This research uses a type of research with survey method, i.e. research by obtaining data from a particular place that is natural (not man-made), but the researcher did treatment in data collection. This research was conducted with a sample of as many as 216 respondents. Technique of data analysis in this study is by using Structural Equation Modeling equations model PLS (Partial Least Square) with the program WarpPLS 5.0. The results showed the leadership style of the principal effect is positive towards the career development 0.62, the work motivation gives positive effect of towards the career development 0.65, discipline gives a positive effect towards the career development 0.69, work motivation mediated the influence of principal leadership style towards the career development 0.40, the work motivation mediate the influence of principal leadership style towards the career development 0.50, and discipline mediated the influence of principal leadership style towards the career development at SMK in Boyolali district in the academic year of 2014/2015 0.31. Work motivation test results mediated the influence of principal leadership style towards the career development by using VAF method i.e. 23.03%. Work motivation mediated the discipline influence towards the career development that is 19.01%. Discipline mediated the influence of principal leadership style towards the career development i.e. 31.15%. The result value of R² principal leadership style towards the career development is 38.44%, the work motivation towards the career development is 42.25%, and discipline towards the career development is 47.61%.